IMPACT OF TOURISM IN ALAMENDAH TOURISM VILLAGE ON THE PHYSICAL, ECONOMIC, SOCIAL AND CULTURAL ENVIRONMENT OF LOCAL COMMUNITIES - Ramadhani, Zaki Alif; Darajat, Muhammad Nur Ali; Adiyoso, Muhammad; Zidany, Naufalika Anggi; Alidha, Seprina Yana (Sebatik, 2023)
A tourist village is one or more administrative areas with defined limits where the local population manages the tourism-related products. An endeavour to use natural or cultural resources as a tourist attraction is called tourism development. One strategy for implementing community-based and sustainable tourist development, particularly in rural regions, is the creation of tourism communities. One of the villages with a concentration on agro- and nature-based tourism is Alamendah Village, which is operated as a tourist village. Tourism's expansion and growth will undoubtedly have a direct and indirect impact on the neighborhood and its surroundings. In Alamendah Village, Bandung Regency, West Java, this study intends to examine the effects of creating a tourist village on the sociocultural, economic, and physical aspects of the local community. An approach known as the qualitative-descriptive approach was used for this study. By building on observational techniques and performing a web search for documentation studies pertaining to the influence of tourism growth in Alamendah Village, data was collected. According to the study's findings, the Alamendah Tourism Village's tourism-related activities had a good impact on the local community's sociocultural and economic circumstances while having no adverse effects on the surrounding environment.